BS ISO 2928. Rubber hoses and hose assemblies for liquefied petroleum gas (LPG) in the liquid or gaseous phase and natural gas up to 2, 5 MPa (25 bar). Specification. (18th March 2020) - British Standards Institution,
No abstract available